Highlighting the Reversible Manganese Electroactivity in Na‐Rich Manganese Hexacyanoferrate Material for Li‐ and Na‐Ion Storage. Issue 1 (25th September 2019) - Mullaliu, Angelo; Asenbauer, Jakob; Aquilanti, Giuliana; Passerini, Stefano; Giorgetti, Marco
Abstract: The electroactivity of sodium‐rich manganese hexacyanoferrate (MnHCF) material constituted of only abundant elements, as insertion host for Li‐ and Na‐ions is herein comprehensively discussed. This material features high specific capacities (>130 mAh g −1 ) at high potentials when compared to other materials of the same class, i.e., Prussian blue analogs. The reversible electronic and structural modifications occurring during ion release/uptake, which are responsible for such high specific capacity, are revealed herein. The in‐depth electronic and structural analysis carried out combining X‐ray diffraction and X‐ray absorption spectroscopy (XAS), demonstrates that both Fe and Mn sites are involved in the electrochemical process, being the high delivered capacity the result of a reversible evolution in oxidation states of the metallic centers (Fe 3+ /Fe 2+ and Mn 2+ /Mn 3+ ). Along with the Mn 2+ /Mn 3+ oxidation, the Mn local environment experiences a substantial yet reversible Jahn–Teller effect, being the equatorial Mn‐N distances shrunk by 10% (2.18 Å → 1.96 Å). Na‐rich MnHCF material offers slightly higher performance upon uptake and release of Na‐ions (469 Wh kg −1 ) than Li‐ions (457 Wh kg −1 ), being, however, the electronic and structural transformation independent of the adopted medium, as observed by XAS spectroscopy. Abstract : Manganese hexacyanoferrate features electroactivity from both metallic sites, i.e., Mn and Fe, the thus the electrochemical capacity is enhanced. Local environments are affected during the release/uptake of Li + and Na + ions, in particular the Mn site is subjected to a considerable but reversible Jahn–Teller effect. The flat electrochemical profile at high potentials displayed in Na half‐cells offers high energy performance.